2011
DOI: 10.3325/cmj.2011.52.469
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in patterns of relations between family interactions and depressive symptoms in adolescents

Abstract: AimTo gain insight into the relations between protective/risk family interactions and depressive symptoms in adolescent boys and girls.MethodA self-reported cross-sectional survey was conducted on a representative sample of 1191 secondary school students (617 girls and 574 boys) aged from 14 to 19 years, with a median of 16, from all secondary schools in the Primorsko-goranska County, Croatia in January and February 2010. Students reported their depressive symptoms, perceptions about the relationship with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Furthermore, both perceived quality of the relationship with the father and mother presented a negative effect on depressive symptoms scores at every time point of the study. The gender effect on depressive symptoms was associated with a gender effect on the father–adolescent relationship such that the worse relationship between girls and their father partly explained the higher scores in depressive symptoms in each assessment time among girls; this finding confirms our expectations and aligns with research by Smojver-Ažić and Bezinović (2011) and Reeb and Conger (2009). A latent growth curve model integrating the change in study variables showed that the increase in depressive symptoms was associated with the decreases in both father–adolescent relationship and mother–adolescent relationship quality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, both perceived quality of the relationship with the father and mother presented a negative effect on depressive symptoms scores at every time point of the study. The gender effect on depressive symptoms was associated with a gender effect on the father–adolescent relationship such that the worse relationship between girls and their father partly explained the higher scores in depressive symptoms in each assessment time among girls; this finding confirms our expectations and aligns with research by Smojver-Ažić and Bezinović (2011) and Reeb and Conger (2009). A latent growth curve model integrating the change in study variables showed that the increase in depressive symptoms was associated with the decreases in both father–adolescent relationship and mother–adolescent relationship quality.…”
Section: Discussionsupporting
confidence: 90%
“…Communication between adolescents and their father seems to vary by gender, and these difficulties appear to be more strongly related to internalizing problems for girls than for boys (Demidenko, Manion, & Lee, 2015). In a study of Croatian adolescents, depressive symptoms in girls were more closely linked to a lack of protective family factors, whereas depressive symptoms in boys were more closely linked to the existence of harmful family factors (Smojver-Ažić & Bezinović, 2011). A meta-analysis by Kane and Garber (2004) highlighted gender differences in the association between paternal mental health, the father–adolescent relationship, and certain adolescent mental health outcomes.…”
mentioning
confidence: 99%
“…First author, year and country Children Auerbach (2011) Canada 16 La Greca & Harrison (2005) USA 60 Auerbach (2011) Canada 16 Minkkinen (2014) Finland 67 Rueger (2010) USA 84 Smojver-Azic (2011) Croatia 96 Smojver-Axic (2011) Croatia 96 Tummala-Narra (2013) USA 103 Auerbach (2011) Canada 16 Hall-Lande (2007) USA 49 La Greca & Harrison (2005) USA 60 Minkkinen (2014) Finland 67 Rueger, 2010 USA 84 Auerbach (2011) Canada 16 Murberg ( 19 Okun (1998) USA 70 Simon (2010) USA 93 Fiori (2006) USA 37 Okun (1998) 70 Bullers (2000) USA 22 Okun (1998) USA 70 Bullers (2000) USA 22 Aro (2001) Finland 15 Bullers (2000) USA 22 Subtotal Elderly Antonucci (1997) France 13 Cacioppo (2006) USA (study 1) 23 Cacioppo (2006) USA (study 2) 23 Fiori (2006) USA 37 Park (2014) USA 75 Choi (2011) USA 24 Dean (1990) USA 30 Fernandez (1998) USA 36 Choi (2011) USA 24 Dean (1990) USA 30 Fiori (2006) USA 37 Zunzunegui (2001) Spain 112 Dean (1990) USA 30 Fiori (2006) USA 37 Palinkas (1990) USA 74 Antonucci (1997) France 13 Oxman (1992) USA 73 Zunzunegui ( used a unique social support meas...…”
mentioning
confidence: 99%
“…ATP surveys are primarily completed by mothers (>85%), and this suggests warmth from the same-gender parent may be particularly important. Other research has found warmth provided by fathers to be one of the strongest protective factors against depressive symptoms for adolescent boys (Smojveri-Aži c & Bezinovi c, 2011). Given that these developmental periods are marked by transitions in social identity (Tanti, Stukas, Halloran, & Foddy, 2011) and pubertal processes, it is plausible that warmth from a parent who has experienced similar physiological and social changes is reassuring during this developmental stage.…”
Section: Discussionmentioning
confidence: 99%